Contextual socioeconomic determinants of cardiovascular risk factors in rural south-west China: a multilevel analysis - Geater Alan; Chongsuvivatwong Virasakdi; Le Cai (BMC, 2007)
Abstract Background We examined independent influences of contextual variables on cardiovascular risk factors in Shilin county, Yunnan province, South-west China. Methods Three villages were selected from each of the ten townships based on probability proportional to size. In each selected village, 200 individuals aged ≥ 45 years were chosen based on simple random sampling method. From 6006 individuals, information on demographic characteristics, smoking and drinking status was obtained by interview. Blood pressure, height, weight, and waist and hip girth were measured. Fasting blood sugar was measured in a 10-percent subsample. Contextual data were from official reports. Multi-level regression modelling with adjustment for individual and contextual variables was used. Results Contextual variables associated with CVD risk factors included: remoteness of village with higher blood pressure and fasting blood sugar, high proportion of Yi minority with drinking, high literacy rate with a lower rate of smoking and a lower mean waist-hip ratio, and high average income with lower systolic blood pressure and body mass index (BMI) but higher FBS. Conclusion While contextual SES is associated with a few CVD risk factors, villages with high level of income are worse off in fasting blood sugar. Strategies of economic development should be reviewed to avoid adverse effects on health.